Environmental Issues in Nevada Barr's Crime Fiction - Pohořálková, Šárka (Univerzita Pardubice, 2025)
This bachelor thesis explores the depiction of the environment and environmental issues in the detective fiction of the American author Nevada Barr. The thesis describes the genre of crime fiction and the literary discipline of ecocriticism, explores the understanding of what wilderness is, and further analyses and compares the novels Track of the Cat and Ill Wind, primarily based on the findings from the previous chapters.
Environmentální problematika v detektivní fikci Nevady Barr
Keywords: environmentální literatura; detektivní fikce; národní parky; divočina; ekokritika; Nevada Barr; environmental writing; crime fiction; national parks; wilderness; ecocriticism; Nevada Barr